An Insight into Green Brand Equity; It’s Predictors and Outcomes - Mustansar Imam Shah; Jibran Majeed; Batish Javed; Afshan Reham; Mehtab Anwar (UW Journal of Management Sciences, 2022)
Purpose: The purpose of this research was to examine antecedents and outcomes of green brand equity in the automobile sector. Design/Methodology: Data was collected through 314 automobile users of four cities of Pakistan, i.e. Lahore, Multan, Faisalabad and Rawalpindi. SPSS 23 and AMOS 23 were used for the statistical analysis of the data. Findings: Findings indicated that green brand image was positively related to green brand equity. green trust and green satisfaction mediated this positive link. Moreover, green brand equity further positively related to brand attitude, brand preference, positive word of mouth and purchase intention. Limitations: The sample size was relatively low. The data was collected from only four cities. Only four consumer responses were studied. The study was sectorspecific. Practical implications: Marketers can focus on developing the environmental equity of the brand as it positively affects the responses of the consumer. Therefore, green brand equity of the brand results in responses that lead towards higher sales, increasing the profitability of the business. Originality/value: The study incorporates consumer responses as the consequences with the green brand equity model.